2017
DOI: 10.1007/s10792-017-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central corneal thickness with four different optical devices

Abstract: 2016/112.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Maresca et al [7] Scheimpflug camera and USP Significant High correlation Not interchangeable Scotto et al [8] OCT, non-contact specular Significant Poor repeatability Not interchangeable microscopy, and UPS Binnawi et al [10] OCT, pachymetry, and Significant High correlation Not interchangeable TMS-5 topography Dogan et al [11] Scheimpflug-Placido Significant High repeatability Not interchangeable topography, OCT, optical biometry, and USP González-Pérez et al [12] USP, non-contact Significant High repeatability Interchangeable except tono/pachymetry, Pentacam except tono-pachymetry tono/pachymetry corneal topography, and OCT Gokcinar et al [13] OCT, corneal topography, Significant -Not interchangeable optical biometry, specular microscopy, and USP Teberik et al [14] Pentacam HR, Sirius -High consistency Interchangeable topography, iPac, and Echoscan US-500 Mansoori et al [15] OCT, optical biometry, and Significant -A high level of agreement Sirius anterior segment analysis between optical biometry and Sirius topography, but not OCT Kiraly et al [16] IOL Master 700, Pentacam HR, Significant Not interchangeable and Cirrus HD-OCT Ozyol and Ozyol [17] SD-OCT with Scheimpflug Non-significant -Interchangeable system, optical biometry, and non-contact pachymetry Erdur et al [18] Ultrasonic pachymetry, SD-OCT, and Non-significant Strong correlation Interchangeable non-contact specular microscopy Calvo-Sanz et al [19] OCT, non-contact specular Significant -OCT and USP offered highly microscopy, and USP comparable results, but not non-contact specular microscopy Bayhan et al [20] SD-OCT, Sirius Scheimpflug-Placido topographer, Lenstar optical low-coherence reflectometry, and USP Non-significant Correlated closely Interchangeable HD-OCT: High-definition optical coherence tomography; OCT: Optical coherence tomography; SD-OCT: Spectral domain optical coherence tomography; USP: Ultrasound pachymetry. 10) compared the CCT measurements of OCT, pachymetry, and Scheimpflug-Placido topography using the TMS-5 device (Tomey GmbH, Nürnberg, Germany) in 122 eyes and reported a statistically significant difference in the mean CCT value between the methods, although there was a significant and strong correlation between them.…”
Section: Difference Correlation or Repeatability Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maresca et al [7] Scheimpflug camera and USP Significant High correlation Not interchangeable Scotto et al [8] OCT, non-contact specular Significant Poor repeatability Not interchangeable microscopy, and UPS Binnawi et al [10] OCT, pachymetry, and Significant High correlation Not interchangeable TMS-5 topography Dogan et al [11] Scheimpflug-Placido Significant High repeatability Not interchangeable topography, OCT, optical biometry, and USP González-Pérez et al [12] USP, non-contact Significant High repeatability Interchangeable except tono/pachymetry, Pentacam except tono-pachymetry tono/pachymetry corneal topography, and OCT Gokcinar et al [13] OCT, corneal topography, Significant -Not interchangeable optical biometry, specular microscopy, and USP Teberik et al [14] Pentacam HR, Sirius -High consistency Interchangeable topography, iPac, and Echoscan US-500 Mansoori et al [15] OCT, optical biometry, and Significant -A high level of agreement Sirius anterior segment analysis between optical biometry and Sirius topography, but not OCT Kiraly et al [16] IOL Master 700, Pentacam HR, Significant Not interchangeable and Cirrus HD-OCT Ozyol and Ozyol [17] SD-OCT with Scheimpflug Non-significant -Interchangeable system, optical biometry, and non-contact pachymetry Erdur et al [18] Ultrasonic pachymetry, SD-OCT, and Non-significant Strong correlation Interchangeable non-contact specular microscopy Calvo-Sanz et al [19] OCT, non-contact specular Significant -OCT and USP offered highly microscopy, and USP comparable results, but not non-contact specular microscopy Bayhan et al [20] SD-OCT, Sirius Scheimpflug-Placido topographer, Lenstar optical low-coherence reflectometry, and USP Non-significant Correlated closely Interchangeable HD-OCT: High-definition optical coherence tomography; OCT: Optical coherence tomography; SD-OCT: Spectral domain optical coherence tomography; USP: Ultrasound pachymetry. 10) compared the CCT measurements of OCT, pachymetry, and Scheimpflug-Placido topography using the TMS-5 device (Tomey GmbH, Nürnberg, Germany) in 122 eyes and reported a statistically significant difference in the mean CCT value between the methods, although there was a significant and strong correlation between them.…”
Section: Difference Correlation or Repeatability Conclusionmentioning
confidence: 99%
“…Other studies have reported results similar to our findings. Teberik et al (15) investigated the consistency of the average scores of CCT measurements using the Pentacam HR, Sirius topography, iPac (Reichert Technologies Inc., Depew, NY, USA) and Echoscan US-500 (Nidek Co., Ltd., Tokyo, Japan) devices, and determined that the high level of consistency indicated that they could be used as alternatives to one another. Mansoori et al (16), who compared CCT measurements of OCT, Sirius optical biometry, and anterior segment analysis, concluded that although there was a high level of agreement between optical biometry and Sirius topography, there was a low level of agreement between OCT and the other methods.…”
Section: Difference Correlation or Repeatability Conclusionmentioning
confidence: 99%
“…Also, these measurements are important for managing corneal pathologies such as ectasia to evaluate the progression of corneal thinning and measuring curvature values 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%